2019
DOI: 10.12659/aot.912005
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Interventions in Vascular Complications After Simultaneous Pancreas and Kidney Transplantations: A Single-Center Experience

Abstract: Background Vascular failures are serious complications in pancreas transplantation. Open surgery is a reliable and quick intervention method, but it carries a risk of infection and bleeding. Endovascular procedures are rare among patients after a SPK, but are becoming more frequently used. One of the main risks of the endovascular approach is that the renal function impairment caused by contrast agent. Material/Methods We performed a retrospective analysis of 200 transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
(43 reference statements)
0
7
0
1
Order By: Relevance
“…Risk factors for amputation after SPK in the MacCraith study included coronary disease 1 . Most recently in 2019, investigators from a single center in Poland published a report of endovascular interventions following pancreas transplantation; among 200 patients, endovascular intervention was required in 3% 3 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Risk factors for amputation after SPK in the MacCraith study included coronary disease 1 . Most recently in 2019, investigators from a single center in Poland published a report of endovascular interventions following pancreas transplantation; among 200 patients, endovascular intervention was required in 3% 3 …”
Section: Discussionmentioning
confidence: 99%
“…In addition to pancreatic insufficiency and ESRD, patients with type 1 DM are also at high risk of lower extremity (LE) peripheral artery disease (PAD), both before and after transplant 1 . The development of PAD is a significant source of morbidity for SPK recipients 1‐4 . One of the earliest studies examining this phenomenon was published in 2003; in a cohort of 200 SPK recipients with type 1 DM, the authors reported an amputation incidence of 6.5% prior to SPK compared with 9.5% after SPK and identified pre‐transplant amputation and duration of dialysis as significant risk factors associated with post‐transplant amputation 4 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Еще в одном случае у пациента с повторной трансплантацией в раннем послеоперационном периоде был выявлен стеноз общей подвздошной артерии проксимальнее анастомоза, в связи с чем было выполнено эндоваскулярное стентирование артерии. При контрольном исследовании повторного стеноза выявлено не было [8].…”
Section: методики восстановления селезеночной и верхней брыжеечной артерийunclassified
“…Although there is still a lack of reliable data due to the relatively little experience of this approach in pancreas transplant complications, endovascular procedures are becoming more frequently used as they are safe and feasible, but technically demanding. One of the main risks of this approach is the renal function damage caused by contrast agent, but the risk of kidney graft function deterioration, as well as of bleeding due to the high dose of heparin used, seems to be lower than with open surgery[ 36 ].…”
Section: Pseudoaneurysmmentioning
confidence: 99%